Assessment of Bony Union following Surgical Stabilisation for Lumbar Spondylolysis: A Comparative Study between Radiography and Computed Tomography - VS Pai; B Hodgson (Journal of Orthopaedic Surgery, 2006)
Purpose. To compare the status of bony union seen on plain radiography versus computed tomography (CT) following tension band repair for refractory spondylolysis. Methods. 14 patients (12 men and 2 women; mean age, 23 years; age range, 16–56 years) with a mean follow-up period of 6.35 years were included. All patients were operated on by one senior surgeon using either a Scott procedure (n=2) or van Dam modification of the Scott procedure (n=12). Bony union of the pars was assessed using both plain radiography (anteroposterior, lateral, and oblique views) and reverse gantry CT. The presence of bony union was determined if a bridging bone was shown in the images. The Oswestry Disability Index was measured at 6-year follow-up. Results. 13 (93%) of 14 patients showed bony union on plain/oblique radiographs versus 7 (50%) on CT scan. The mean Oswestry Disability Index was 28 (good to excellent). The high incidence of nonunion shown on CT scanning did not correlate well with clinical results. Conclusion. Bony nonunion is more difficult to visualise on plain radiographs than reverse gantry CT. CT demonstrates more clearly the presence or absence of the bridging bone. Clinical results do not correlate with bony union, indicating that bony union is not required to achieve good results.